INVENTORY MANAGEMENT: A CASE STUDY IN A TEXTILE INDUSTRY IN THE MUNICIPALITY OF NOSSA SENHORA DO SOCORRO/SE - Santos, Elisângela Auxiliadora Correa; de Souza, Heloísa Thais Rodrigues (Seven Editora, 2026)
This research focuses on the management of finished goods inventory in a textile company in Nossa Senhora do Socorro/SE, with an emphasis on identifying and improving internal logistics processes. The research problem relates to failures in inventory control and accuracy, mainly caused by a lack of standardization, inadequate layout, discrepancies between physical and system inventory, and a high dependence on manual entries, negatively impacting productivity, operational costs, and customer service levels. Given this context, the overall objective of the work was to analyze the flow and propose improvements in the company's inventory management, while the specific objectives consisted of analyzing the current process, identifying the main causes of the failures, applying quality tools, and proposing a new inventory management system aligned with the organizational reality. The research was guided by the theoretical-methodological current of production and logistics management, based on classic authors in the field, and was characterized as applied research, descriptive in nature, with a mixed-methods approach, using the case study method. The methodological procedures included bibliographic and documentary research, as well as direct observation of operational processes. As a result, it was found that the application of quality tools enabled a structured analysis of existing failures and supported the proposal of practical improvements. Key improvements included the reorganization of the stock layout, implementation of addressing systems, use of visual management, adoption of monthly rotating inventories based on the ABC Curve, and the proposed automation of movements through scanning integrated with the ERP system. These actions contributed to increased inventory accuracy, reduction of operational errors, decreased rework and waste, improved order picking speed, and strengthened control of logistics information. It is concluded that the proposed objectives were achieved, demonstrating that the new inventory management system significantly contributed to operational efficiency, internal organization, and the company's competitiveness in the market.